The effects of recovery modalities including ice bath immersion on recovery from exercise and subsequent performance - Fitzpatrick, P.; Warrngton, G. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to examine the effects of recovery modalities on recovery and subsequent performance. Ten trained male rugby union players were tested three times completing a different, randomly assigned recovery modality on each occasion. Each test began with a maximal aerobic endurance field test (20 metre shuttle test) followed by one of three recovery strategies - passive recovery, active recovery or ice bath immersion. Passive recovery involved lying on a recovery bed for 20 mins; active recovery entailed cycling for 20 mins at 50% heart rate reserve; and ice bath immersion required subjects to sit waist deep in an ice bath (5-8°C) for 3 x 30 s repetitions separated by one minute standing outside the bath. Following the 45 minute post-recovery strategy period, subjects completed 6 shuttles of a timed performance test (Illinois agility test). Plasma lactate concentrations and muscle soreness ratings were measured at various intervals throughout the testing. Analysis of the data revealed that active recovery resulted in significantly greater rates of lactate removal 5 mins into the recovery strategy when compared to passive recovery (p = 0.01). Muscle soreness was significantly lower for ice bath immersion than for active recovery immediately after the 20 minute recovery period (p = 0.006). No significant differences were observed for the subsequent performance test.